2014
DOI: 10.15669/pnst.4.9
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Cs-134 and Cs-137 in river waters from Fukushima and Gunma prefectures at nine months after the Fukushima Daiichi NPP accident

Abstract: Cs from the watershed to the river waters occurred mainly as particulate forms and that their radioactivity depends on the levels of radioactivity at the watersheds of the respective river systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…This relationship could be the signature of riverine inputs to the coastal areas because the Ukedo River flows through a highly contaminated watershed. However, several authors have emphasized that rivers discharge small amounts of dissolved radiocaesium (Sakuma et al, 2019;Nagao et al, 2014). As mentioned in the Introduction, during the period of our sampling, typhoons #18 (Phanfone) and #19 (Vongfong) made landfall on Japan on 6 and 13 October, respectively.…”
Section: An Estimation Of Initial Activity Concentration Of Freshwater From Landmentioning
confidence: 89%
See 1 more Smart Citation
“…This relationship could be the signature of riverine inputs to the coastal areas because the Ukedo River flows through a highly contaminated watershed. However, several authors have emphasized that rivers discharge small amounts of dissolved radiocaesium (Sakuma et al, 2019;Nagao et al, 2014). As mentioned in the Introduction, during the period of our sampling, typhoons #18 (Phanfone) and #19 (Vongfong) made landfall on Japan on 6 and 13 October, respectively.…”
Section: An Estimation Of Initial Activity Concentration Of Freshwater From Landmentioning
confidence: 89%
“…The result was the transfer of up to 10-12 TBq of radiocaesium from the land to the ocean during the first year after the accident (Evrard et al, 2015). (Nagao et al, 2014) found that about 50% of the radiocaesium in the Niida River was in dissolved form in the first few months after the accident, whereas after September 2011 more than 70% of the radiocaesium was associated with particles, and that percentage was even higher after storms.…”
Section: Introductionmentioning
confidence: 99%
“…It has been necessary to measure dissolved radiocesium ( 134 Cs and 137 Cs) concentrations in freshwater near the Fukushima Daiichi Nuclear Power Plant (FDNPP) since the FDNPP accident to provide information to allow root uptake by crops and accumulation in aquatic organisms to be assessed. Many institutions have therefore monitored dissolved radiocesium concentrations in freshwater in northeastern Japan since the FDNPP accident [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Radionuclide transport processes have been studied in the Abukuma River system [5][6][7] and small rivers in eastern Fukushima Prefecture [8,9]. Ueda et al [10] reported that the radiocesium concentrations depend on the water discharge rates.…”
Section: Introductionmentioning
confidence: 99%